Taman Bacaan Masyarakat sebagai Ruang Edukasi dan Interaksi Sosial dalam Program KKN Kelurahan Marga Mulya - Yuniarsih, Atika; Atsaqifa, Fira; Kusnaedi, Maisie Zabrina; Putri, Sheva Auliya; Putri, Thalita Nailah (Pakis Journal Institute, 2026)
The Community Service Program (KKN) is a form of community service aimed at helping overcome various social problems, particularly in the fields of education and literacy. The low interest in reading among the community encourages the need to provide alternative learning spaces that are easily accessible. This study aims to describe the implementation of the Community Reading Garden (TBM) program as a means of education and social interaction for children in RW 02, Marga Mulya Village. The method used is qualitative research with a descriptive approach through the stages of program planning, implementation, and evaluation. TBM activities are carried out at the Village Hall by involving children from early childhood to elementary school age through reading, writing, counting, coloring, reading together, and character-building activities such as making anti-bullying posters. The results of the activities indicate that the TBM program is able to increase children's interest in learning, participation, and self-confidence. This program also serves as a social space that supports the strengthening of literacy culture and character building in the community.